2019
DOI: 10.1101/632307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell cycle regulators control mesoderm specification in human pluripotent stem cells

Abstract: Mesoderm is one of the three germ layers produced during gastrulation from which muscle, bones, kidneys and the cardiovascular system

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…We hypothesize that this strategy could facilitate rapid switching of methylation states that may be required to eliminate this modification efficiently during early cell fate transitions. For instance, active regulation may support rapid changes in cell cycle-dependent control that are required for the exit from pluripotency towards the early germ layers 48,49 . Simultaneously, these activities would also enable robust activation upon exposure to the appropriate differentiation signals.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this strategy could facilitate rapid switching of methylation states that may be required to eliminate this modification efficiently during early cell fate transitions. For instance, active regulation may support rapid changes in cell cycle-dependent control that are required for the exit from pluripotency towards the early germ layers 48,49 . Simultaneously, these activities would also enable robust activation upon exposure to the appropriate differentiation signals.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 also appears to be necessary for EHT, and for balanced HPC differentiation and survival. Of note, CDKs are known to be involved in a variety of non-canonical functions such as transcriptional control and cell fate decision (39, 42, 43, 44, 45, 68). Accordingly, our results showed that the activation of CDK4/6 and CDK1 is required during EHT.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive endoderm differentiation was induced according to ( Yiangou et al, 2019 ). Cells were cultured in CDM-PVA supplemented with 100 ng/ml Activin A (produced in house), 80 ng/ml FGF2 (produced in house), 10 ng/ml BMP4 (R&D Systems), 10 µM LY294002 (Promega) and 3uM CHIR99021 for one day, with CHIR99021 omitted on the second day.…”
Section: Methodsmentioning
confidence: 99%